(untitled) (Research, Society and Development, 2025)
Asthma and rhinitis are the most frequent allergies in the Brazilian population. Studies showed that individuals with asthma and allergic rhinitis can have a two-fold increased risk of developing otitis media, which points to the importance of the investigations of the auditory function in children with these conditions, because disturbances in auditory development could affect the development of speech, language and learning. The objective of this study was to analyze the results of the auditory function assessment and screening of central auditory processing in children and adolescents with asthma and rhinitis. The sample was composed by 17 patients aged ranged three (3) to 17 years, of both genders, with a clinical diagnosis of asthma and rhinitis. All patients were submitted for basic audiological evaluation with pure tone audiometry and speech audiometry and analysis of acoustic immittance measures, brainstem auditory evoked potential for the analysis of central auditory pathway integrity and screening of central auditory processing by simplified battery. The results revealed peripheral hearing and integrity of central auditory pathways within normal standards, but there was a high frequency of failure in the simplified assessment of central auditory processing. These findings highlight the importance of complementary evaluations and referral for early interventions to reduce the impact of these changes, especially language disorders, on children’s development.